2019
DOI: 10.1021/acsami.8b22563
|View full text |Cite
|
Sign up to set email alerts
|

Black Phosphorus-Based Drug Nanocarrier for Targeted and Synergetic Chemophotothermal Therapy of Acute Lymphoblastic Leukemia

Abstract: As one of the novel two-dimensional nanomaterials, black phosphorus nanosheets (BP NS) have been proven to be excellent carrier materials for drugs, owing to their fine optical properties and biocompatibility. In this work, a composite drug nanocarrier based on BP NS is proposed, which can perform a synergetic and targeted chemophotothermal therapy of acute lymphoblastic leukemia (ALL). First, BP NS were prepared by an improved liquid exfoliation technique. Then, polyethylene glycol (PEG) was modified on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 40 publications
1
45
0
1
Order By: Relevance
“…The colocalization experiment showed that macropinocytosis and caveolae‐dependent pathways were the main ways of the internalization of PEGylated BP nanosheets into cancer cells, which provided some essential guidance for understanding the BP‐based cancer theranostics. The covalent bonding of Sgc8 aptamer on BP nanosheets@PEG attained the highly specific recognition toward the acute lymphoblastic leukemia, and enhanced the endocytosis of drug carriers into cells by a receptor‐mediated manner . The combination of both PTT of PEGylated BP nanosheets and chemotherapy of DOX triggered the remarkable tumor‐inhibited effect.…”
Section: Biomedical Application Of Nano‐bpmentioning
confidence: 99%
“…The colocalization experiment showed that macropinocytosis and caveolae‐dependent pathways were the main ways of the internalization of PEGylated BP nanosheets into cancer cells, which provided some essential guidance for understanding the BP‐based cancer theranostics. The covalent bonding of Sgc8 aptamer on BP nanosheets@PEG attained the highly specific recognition toward the acute lymphoblastic leukemia, and enhanced the endocytosis of drug carriers into cells by a receptor‐mediated manner . The combination of both PTT of PEGylated BP nanosheets and chemotherapy of DOX triggered the remarkable tumor‐inhibited effect.…”
Section: Biomedical Application Of Nano‐bpmentioning
confidence: 99%
“…For example, Zong et al prepared a drug nanocarrier based on BP nanosheets modified by PEG through electrostatic adsorption, which can enhance the stability of bare BP nanosheets and work as a synergetic and targeted chemophotothermal platform for treatment of acute lymphoblastic leukemia (ALL) ( Fig. 2 ) [ 76 ]. Liang et al designed a vesicular preparation of BPQDs coated with red blood cell membranes (RBCM), which can induce apoptosis of breast cancer cells in situ by NIR laser irradiation, thereby mobilizing the immune system to eliminate residual and metastatic cancer cells ( Fig.…”
Section: Biodegradability and Stability Of Bpmentioning
confidence: 99%
“…Liquid phase exfoliated BPNSs can possess a negative zeta potential, which renders it possible to noncovalently functionalize BPNSs with positively charged species (e.g., small molecules, polymers) through electrostatic interactions . For instance, Sabherwal and co‐workers employed nanostructured BP as a platform in an electrochemical sensor for the detection of Myoglobin (Mb), a cardiac disease biomarker.…”
Section: Noncovalent Functionalization Of Bpnssmentioning
confidence: 99%
“…To passivate BPNSs and maintain its functions, effective functionalization strategies must be performed. The outstanding biocompatibility and biodegradability of functionalized BPNSs in physiological environment makes them attractive and promising for wide bioapplications in photodynamic therapy and photothermal therapy, tissue engineering, biosensors, and bioimaging . Qiu et al have developed a new concept of light activation of BPNSs based hydrogel for cancer therapy .…”
Section: Applications Of Functionalized Bpnssmentioning
confidence: 99%